Dynamic force analysis of a six-link planar mechanism under consideration of friction at the joints - Dien, Nguyen Phong; Khang, Nguyen Van (Vietnam Journal of Mechanics, 2004)
The dynamic analysis of mechanisms with joints friction is complex since the frictional force depends nonlinearly on the resultant reactive force between the two mating surfaces of the joint. In this paper a non-iterative approximate method is used for determining the joint reaction forces and the driving torque of mechanisms is considered. By using the computing program MATLAB the dynamic forces of a six-link planar mechanism are calculated with this method.